COOPERATIVISMO, PLANEJAMENTO E GESTÃO DE EQUIPES: A EXPERIÊNCIA DA OCERJ ORGANIZAÇÃO DAS COOPERATIVAS DO ESTADO DO RIO DE JANEIRO - Rodrigues, Sergio Bernardo (2003)
In Brazil cooperatives organization exists regulating entity of the cooperativist system of the country and, through the state organizations, it permanently looks for to endow the system with the necessary conditions to take care of its main objectives. This work has as proposal the study from the experience of the OCERJ, capable to propitiate conditions of external conditions for the cooperatives, in way to improve the operations and managements of the same ones, as well as facilitating the orientation on the part of the OCERJ. For this, chapter 1 presents a revision of scientific literature and the working question, through the existing legislation on the subject, and aims at to show the different boardings of the strategical planning. Chapter 2 presents the methodology of the work, bringing the inherent concepts to the subject. Chapter 3 analyzes the functioning and the structure of the OCERJ, Cooperative of the State of Rio de Janeiro, with a strategical planning for the implementation of a program of quality in the cooperativista system. To the end, some suggestions and recommendations are presented the heading of conclusion of the present study